Numerical Analysis for the Caving Characteristics of Rock Mass with Inclined Joints in Caving Mining - Jinbo Sui; Fengyu Ren; Jianli Cao; Huan Liu (Advances in Civil Engineering)
In caving mining, the successful initiation and propagation of caving require one low-dip joint set. However, not every mine has a low-dip joint set. The Hemushan Iron Mine in China was taken as the engineering background, and the caving characteristics of rock mass with inclined joints were analyzed based on the synthetic rock mass (SRM) model. First, the inclined joints were investigated in the Hemushan Iron Mine. Second, model parameters were determined based on the geological conditions of the mine, and seven models were established. Third, the caving process was simulated, and caving characteristics were monitored. For rock mass with inclined joints after undercutting, the research showed that the crack zone was significant, and the crack zone existed not only around the undercut area but also further away in the model. The stress concentration areas dispersed in the model except for the top of the undercut area. The caving line was not a standard arch, and the highest point of the caving line was biased towards the direction of the undercut. Under the same undercut width, with the decrease of joint length in the joint system, the number of cracks decreased, the degree of stress concentration became weaker, and the height of the caving line decreased.